A chaos-based true random number generator based on OTA sharing and non-flipped folded Bernoulli mapping for high-precision ADC calibration. (October 2021) - Dong, Siwan; Wang, Yarong; Xin, Xin; Tong, Xingyuan
Abstract: An operational amplifier sharing (op-amp sharing), non-flipped folded Bernoulli mapping chaos-based true random number generator (TRNG) is proposed in this paper. Based on the concept of op-amp sharing for non-flipped folded Bernoulli mapping, the number of stages is reduced from two stages to one, which improves power efficiency of the system. Among them, a novel transconductance enhancement recycling amplifier is adopted for power reduction. The entire system has been implemented in a standard 180 nm process with power supply of 1.2V, and the output speed of random number is 500k Bits/s with power consumption of only 4.68 μW. The TRNG system is verified over a wide range of process and temperature variations, including TT corner 25 °C, FF corner 0 °C, and SS corner 85 °C with post-layout simulation. All the generated random bits pass National Institute of Standards and Technology (NIST) SP800-22 randomness tests successfully.